On the Indo-European Origin of the Dual N-Marker in Tocharian - Witczak, Krzysztof (Lingua Posnaniensis, 2012)
Purpose: In my paper I discuss the origin of the dual n-marker in Tocharian (Toch. B -ne, A -m), which seems to denote natural pairs, as well as random twosomes. It is traditionally treated as an innovation of the Tocharian languages. Method: In my investigations I used the historical-comparative method. Results: Some residual facts attested in the different Indo-European languages (including Albanian, Old Prussian and Insular Celtic ones) demonstrate traces of the n-marker. Conclusion: The dual nmarker, preserved in Tocharian, is of Indo-European origin.